Employer Brand and Application Intentions of Young People in Hanoi - Ngoc Thao, Nguyen; Van Luan, Hoang (VNU Journal of Science: Policy and Management Studies; Vol 38 No 3, 2022)
Employer brand is becoming an important factor determining the effectiveness of attracting human resources, especially high-quality human resources of enterprises. Employer branding is built by businesses but its attractiveness is subjective to potential candidates in the specific economic, cultural and social context of the region and country. The article analyzes and inherits published studies to give the concept of employer brand and the elements constituting the remployer brand and the relationship between employer brand with the potential candidate's intention to apply for a job. Survey results on the evaluation of young people in Hanoi about the attractiveness of employer brands are compared with existing research results to show regional differences of employer brands. On the basis of research results, the article makes some conclusions and recommendations related to the construction and communication of employer brand in order to improve the effectiveness of attracting and maintaining human resources of the organization general and businesses in particular. Keywords : Employer Brand, Intention   to   Apply , Young People in Hanoi, Employer Brand Development, Employer   Brand   Communication